Screening method for selecting the potential fungi for use in the bioremediation of leachate - Wan Razarinah, W.A.R (2011)
This study focuses on a screening method for selecting the potential fungi which has ability to be used in bioremediation of leachate. In this study, twelve fungal species were tested for their ability to grow on 50% and 100% leachate incorporated with malt extract agar (MEA) and also the affect of pH medium on fungi growth. The radial growth was measured every 48 h for a period of 30 days after incubation at 30 °C, and the growth rates were determined. Results show no growth was observed by all fungi species on malt extract agar incorporated with 100% leachate except for Ganoderma australe, Trametes menziesii (KUM 7011(54)), Penicillium sp., and Pycnoporus sanguineus. These fungi give growth rates of 6.1 ± 0.8 mm, 5.9 ± 0.6 mm, 2.3 ± 0.3 mm and 0.8 ± 0.3 mm respectively. On 50% leachate, the growth of Trametes menziesii shows the most rapid followed by Ganoderma australe and Penicillium sp. with growth rates of 7.4 ± 0.3, mm 6.9 ± 0.3 mm, and 2.9 ± 0.0 mm respectively. Besides, the comparison growth of Penicillium sp., Trametes menziesii, and Ganoderma australe on the medium at pH 6.0 – 6.5 and nonadjusted pH medium show slightly difference. They give the growth rates of 3.7 ± 0 and 2.9 ± 0, 7.0 ± 0.1 and 7.4 ± 0.3, 6.1 ± 0.3 and 6.4 ± 0.1 respectively. Therefore, these fungi species show the ability to grow on leachate and can be considered to have the potential to be used in the bioremediation of leachate.